Effect Of Herbal Formulation On Motor Functions In Pediatric Spastic Cerebral Palsy-An Open Randomised Controlled Trial - Pai, Preetham; Srivastava, Leena; Gaikwad, Parag; Jadhav, Roopesh (Journal of Neonatal Surgery, 2025)
Spastic cerebral palsy (CP), majorly characterised by muscle stiffness and motor dysfunction, significantly impacts the quality of life of affected individuals and also the relatives of the sufferer. Modern management of cerebral palsy (CP) has significantly improved symptom control and quality of life, but it has several limitations. One of the significant drawbacks is the lack of curative treatment, as current medical approaches focus primarily on managing symptoms rather than reversing brain damage. Seeing challenges, alternative and integrative approaches, including traditional medicine like Ayurveda, may provide a more holistic, accessible, and sustainable solution for managing CP. Ayurvedic medicine offers potential effectiveness for managing such neurological conditions. This study investigates the efficacy of Kalyanak Ghritam (KG), a classical Ayurvedic formulation, in improving motor function and reducing spasticity in children with spastic cerebral palsy. The study was conducted as a randomised, controlled clinical trial with participants in the age group 2–7 years diagnosed with spastic CP. The treatment group received oral administration of KG along with standard physiotherapy, while the control group was treated with physiotherapy alone. The outcomes were assessed using validated tools like the Gross motor milestones, GMFM and Modified Ashworth Scale. The results demonstrated a statistically significant improvement in motor milestones turning over, head holding, crawling and standing and muscle power in the treatment group compared to the control group. KG showed good neuroprotective and muscle-strengthening effects, suggesting its potential as an adjunct therapy in spastic CP management. The study concludes that integrating Ayurvedic herbal formulation like KG with conventional rehabilitation strategies may enhance treatment outcomes in spastic cerebral palsy, finally improving the quality of life of sufferers.